PENDIDIKAN HUMANIORA PESANTREN (ANALISIS SOSIOLOGIS KEBIJAKSANAAN HIDUP KIAI) - M. Lutfi Mustofa (el-hikmah, 2012)
Sociologically, Islamic boarding school (pesantren) is a variant of the sociological institution in Muslim society that have two meanings at once, namely the proximity of synonymous with Islamic significance and originality of Indonesia. Pesantren emerges and develops among the Indonesian sociological community experiences loaded with the values of the humanity. As an institution that is identical with the meaning of the Islamic boarding school, was the institution of religion (tafaqquh fiddin) that concern in the field of Islamic knowledge. That is why, the material taught by the pesantren in general is the Islamic sciences, laden with humanitarian values, especially the Islamic jurisprudence (fiqh) and mysticism or Sufism. This second Islamic material was the center of teachings at pesantren, because he was related to the Mission of the prophetic teachings of Islam. For pesantren and the religious leaders (kiai), the teaching of Islamic jurisprudence and sufism or the morality are the instruments of anticipation of the need for change in world view, which allows its use in pesantren. The teaching of Islamic in pesantren focus more on anticipatory memorial, so that a number of the principle is that limber is expected to steer the social dynamics of the santri, especially in answering the problem of humanity in the midst of modernity.